Performa Sistem Informasi Akuntansi PT Masmedia Buana Pustaka - Putri, Yemima Michelle Dewanti Kusumaning; Pardi (IJESPG (International Journal of Engineering, Economic, Social Politic and Government), 2023)
Knowing how well the organization is performing with the current Accounting Information System is very important. The more efficiently the system runs, the more it helps organizations produce reliable and up-to-date financial reports. The purpose of this study, which relies on secondary data sources, is to identify the relationship between individual technical competency, user participation, top-level management support, and funding for PT Masmedia Buana Pustaka's accounting information system. In this study, a simple random sampling strategy was used to collect a sample size of 50 people by administering a questionnaire. Multiple linear regression analysis (multiple regression) was used as a quantitative research methodology for this study. According to research findings, the performance of Accounting Information Systems at PT Masmedia Buana Pustaka is above average in several key areas, including personal technical competence, user engagement, top management support, and funding. Abstrak Mengetahui seberapa baik kinerja organisasi dengan Sistem Informasi Akuntansi saat ini sangat penting. Semakin efisien sistem berjalan, semakin membantu organisasi menghasilkan laporan keuangan yang andal dan terkini. Tujuan dari penelitian ini, yang mengandalkan sumber data sekunder, adalah untuk mengidentifikasi hubungan antara kompetensi teknis individu, partisipasi pengguna, dukungan manajemen tingkat atas, dan pendanaan untuk sistem informasi akuntansi PT Masmedia Buana Pustaka. Dalam penelitian ini, strategi pengambilan sampel acak sederhana digunakan untuk mengumpulkan ukuran sampel 50 orang melalui pemberian kuesioner. Analisis regresi linier berganda (multiple regression) digunakan sebagai metodologi penelitian kuantitatif untuk penelitian ini. Menurut temuan penelitian, kinerja Sistem Informasi Akuntansi di PT Masmedia Buana Pustaka berada di atas rata-rata di beberapa bidang utama, termasuk kompetensi teknis pribadi, keterlibatan pengguna, dukungan manajemen puncak, dan pendanaan.